High-Performance Computing on Wall Street. - Spiers, Brad; Wallez, Denis (Computer (00189162), 2010)
Financial institutions could achieve a two- orders-of-magnitude optimization by utilizing parallel computing for their applications. If programmers can meet the software challenges, parallelization could dramatically reshape computational finance for years to come.